DNA copy number alterations in central primitive neuroectodermal tumors and tumors of the pineal region: an international individual patient data meta-analysis - Bueren, André von; Remke, Marc; Korshunov, Andrey; Pfister, Stefan (Journal of neuro-oncology, 2012)
Little is known about frequency, association with clinical characteristics, and prognostic impact of DNA copy number alterations (CNA) on survival in central primitive neuroectodermal tumors (CNS-PNET) and tumors of the pineal region. Searches of MEDLINE, Pubmed, and EMBASE—after the original description of comparative genomic hybridization in 1992 and July 2010—identified 15 case series of patients with CNS-PNET and tumors of the pineal region whose tumors were investigated for genome-wide CNA. One additional case study was identified from contact with experts. Individual patient data were extracted from publications or obtained from investigators, and CNAs were converted to a digitized format suitable for data mining and subgroup identification. Summary profiles for genomic imbalances were generated from case-specific data. Overall survival (OS) was estimated using the Kaplan-Meier method, and by univariable and multivariable Cox regression models. In their overall CNA profiles, low grade tumors of the pineal region clearly diverged from CNS-PNET and pineoblastoma. At a median follow-up of 89 months, 7-year OS rates of CNS-PNET, pineoblastoma, and low grade tumors of the pineal region were 22.9 ± 6, 0 ± 0, and 87.5 ± 12 %, respectively. Multivariable analysis revealed that histology (CNS-PNET), age (≤2.5 years), and possibly recurrent CNAs were associated with unfavorable OS. DNA copy number profiling suggests a close relationship between CNS-PNET and pineoblastoma. Low grade tumors of the pineal region differed from CNS-PNET and pineoblastoma. Due to their high biological and clinical variability, a coordinated prospective validation in future studies is necessary to establish robust risk factors.
Published online: 7 July 2012
Gesehen am 27.07.2018